Design issues for an ultra compact tapered mmi coupler based 3 db splitter - Kalli, Kyriacos; Themistos, Christos; Rajarajan, Muttukrishnan (My University, 2003)
The design issues for an ultra compact tapered MMI coupler based 3 dB splitter were discussed. A finite-element based beam propagation approach was used to analyze the optical properties of parabolically tapered multimode interference based 3 dB splitters on a deeply etched rib waveguide structure on a InP based material system. It was concluded that the tapered structure is superior than the straight MMI structure, for the same initial width, only as far as length concerned, and the choice of using tapered devices in specific applications is a trade-off between the length and other properties such as image quality and power loss.
Keywords: Finite element method; Interferometers; Optical communication